LEVEL CROSSING RATE OF MACRODIVERSITY WITH THREE MICRODIVERSITY SC RECEIVERS OVER GAMMA SHADOWED NAKAGAMI-M CHANNEL - Petković, Goran; Panić, Stefan; Jakšić, Branimir (Bulletin of Natural Sciences Research, 2016)
Macrodiversity system with macrodiversity selection combining (SC) receiver and three microdiversity SC receivers operating over Gamma shadowed Nakagami-m multipath fading environment is considered in this work. Level crossing arte of signals at outputs microdiversity SC receivers are calculated and by using these formulas, closed form expression for average level crossing rate of macrodiversity SC receiver output signal is evaluated. Average fade duration of proposed macrodiversity system can be calculated as ratio of outage probability and level crossing rate. By using obtained results the influence of Nakagami-m multipath fading severity parameter, Gamma shadowing severity parameter and shadowing correlation parameter on average level crossing rate is analyzed and discussed.